Effects of simulated primary moult on pigeon flight - Bridge, E. S. (Ornis Fennica, 2003)
Quantifying the costs and benefits of flight feather replacement is vital to our understanding of avian moulting patterns and life histories. This study investigated the effects of simulated primary moult on the flight ability of pigeons (Columbia livia domestica) by examining flight performance before and after removing measured lengths of either the innermost or outermost three primaries. All flight sessions were videotaped and took place in a large metabolic chamber, allowing for simultaneous measurement of flap rates, flight velocities, and metabolic rates. Simulated moult gaps of both types increased wing loading by approximately 10% and caused increases in flap rate and flight velocity of about 7% and 8% respectively. Metabolic rate was not significantly affected by the presence of simulated moult gaps. There was no detectable difference between the two moult-gap treatments with regard to aerodynamic or metabolic measurements. In general, the detrimental effects of moult gaps were minor, suggesting that the birds may be able to make biomechanical adjustments to compensate for the loss of wing area.